Detection of additional abnormalities or co-morbidities in women with suspected intrahepatic cholestasis of pregnancy. (December 2020) - Conti-Ramsden, Frances; McEwan, Michael; Hill, Rachel; Wade, Julie; Abraham, Georgina; Buckeldee, Olivia; Williamson, Catherine; Knight, Caroline L; Girling, Joanna; Chappell, Lucy C
Background: Current guidelines recommend viral, autoimmune, coagulation and liver ultrasound testing in intrahepatic cholestasis of pregnancy to exclude alternative diagnoses. Methods: Electronic health records were searched for investigations and diagnoses in women with raised bile acid concentrations (>10 µmol/L) between January 2016 and December 2017 at two UK maternity units. Results: Five hundred and thirty-one women had a raised bile acid concentration (median (IQR): 18 (13–32 µmol/L)) at a median gestation of 35.1 (IQR 31.8–37.0) weeks. Out of 531 women, 250 (47.1%) had full virology, autoimmune and ultrasound tests, and 348 (65.5%) had coagulation performed. Positive hepatitis B and C results were previously known. No new Epstein–Barr virus, cytomegalovirus or hepatitis A diagnoses were made. There were 11 positive autoimmune results, but no new diagnoses. No woman had an unexplained prolonged prothrombin time. No ultrasound liver ( n  = 38) or gallbladder ( n  = 85) abnormalities were of acute clinical significance. Conclusion: Intrahepatic cholestasis of pregnancy investigations provided no new diagnoses that influenced clinical management during pregnancy.